2014
DOI: 10.1177/1087054714548033
|View full text |Cite
|
Sign up to set email alerts
|

External Validity of ADHD Inattention and Sluggish Cognitive Tempo Dimensions in Spanish Children With ADHD

Abstract: The findings support SCT to be a construct with two dimensions that have unique correlates relative to each other as well as ADHD-IN. Future research on SCT should separate these dimensions of SCT to provide a better understanding of the construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 29 publications
8
52
1
4
Order By: Relevance
“…Interestingly, in the regression analyses SCT remained significantly associated with depression but not anxiety. This finding adds to a small but growing body of research indicating that while SCT is clearly associated with internalizing symptoms, this seems to be more specific to depression as opposed to anxiety (Barkley, 2013, Becker et al, 2014a, Fenollar Cortés et al, 2014, Garner et al, 2013, Jacobson et al, 2012). Depression and anxiety are both characterized by high negative affect, but can be differentiated based on physiological hyperarousal (anxiety) or low positive affect/anhedonia (depression) (Anderson and Hope, 2008, Clark and Watson, 1991).…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, in the regression analyses SCT remained significantly associated with depression but not anxiety. This finding adds to a small but growing body of research indicating that while SCT is clearly associated with internalizing symptoms, this seems to be more specific to depression as opposed to anxiety (Barkley, 2013, Becker et al, 2014a, Fenollar Cortés et al, 2014, Garner et al, 2013, Jacobson et al, 2012). Depression and anxiety are both characterized by high negative affect, but can be differentiated based on physiological hyperarousal (anxiety) or low positive affect/anhedonia (depression) (Anderson and Hope, 2008, Clark and Watson, 1991).…”
Section: Discussionmentioning
confidence: 51%
“…Whereas studies show SCT symptoms to remain positively associated with internalizing symptoms when controlling for ADHD inattention symptoms, several studies found SCT to be unassociated or negatively associated with hyperactive-impulsive and externalizing symptoms when controlling for ADHD inattention 14,20,24,25,3033,42 . In contrast, ADHD inattention remains associated with hyperactive-impulsive and externalizing symptoms when controlling for SCT symptoms, pointing to an important double dissociation of SCT and ADHD inattention symptoms that provides further support for the distinctiveness of SCT from ADHD.…”
Section: Resultsmentioning
confidence: 93%
“…Table 4 summarizes meta-analytic results of all available studies that examined the reliability of measures of SCT (Table S2, available online, lists all studies included in these summary statistics). For studies that reported results separately for different SCT factors (e.g., 14,25 ), the mean of these results was included as the single effect from the study. All analyses were repeated with and without these studies included in the analysis, and the overall pattern of results did not change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore perhaps not surprising that SCT was unrelated to poor study skills in this domain since SCT is not characterized by rushing and impulsive behaviors but rather slowed behavior and thinking (Barkley, 2014; Becker, 2013; Becker, Leopold et al,2016). Thus, the slow aspect of SCT may be a primary contributor to academic problems even when comprehension is high (Becker, Ciesielski, et al, 2016; Fenollar Cortés, Servera, Becker, & Burns, 2014; Langberg, Becker, & Dvorsky, 2014; Tamm et al, 2016). Additional research will be needed to replicate the differential finding of the present study that SCT impacts the affective learning and goal strategies study skills domains but not the comprehension monitoring domain.…”
Section: Discussionmentioning
confidence: 99%